2010
DOI: 10.1093/ejo/cjq140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the functional regulator III on transversal changes: a postero-anterior cephalometric and model study

Abstract: Studies assessing the transversal treatment changes caused by the functional regulator III (FR-3) are limited in number. This clinical study was planned to analyse the transversal effects of the FR-3 appliance therapy. The treatment group consisted of 17 patients (8 males and 9 females) with Class III malocclusion, who were treated with the FR-3 appliance. The control group consisted of 17 subjects (7 males and 10 females) with a normal occlusion. Mean ages of the subjects were 10.73 and 10.66 years in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The primary objective of class III malocclusion treatment should be focused on soft tissue profile and appearance rather than occlusion, as opposed to other malocclusion groups [12,13]. Soft tissue response to FM therapy has been investigated in previous studies [4,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of class III malocclusion treatment should be focused on soft tissue profile and appearance rather than occlusion, as opposed to other malocclusion groups [12,13]. Soft tissue response to FM therapy has been investigated in previous studies [4,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have observed substantial effects due to FR-3 appliance's treatment on the maxillary basal bone (Levin et al, 2008). On the other hand, some scholars claimed that the correction of a Class III malocclusion is produced mainly by the clockwise rotation of the mandibular and/or the alterations in upper and lower incisors inclinations (Kilic et al, 2011;Yang et al, 2014). After the treatment of FR-3 appliance in our study, MP-FH, ANS-Me and ANS-Me/N-Me showed a statistically significant increase, demonstrating that the FR-3 appliance can produce the mandible to rotate backward and downward, which is beneficial to improve the general class III concave facial profile, but it should be used with caution in the high-angle patient to prevent the occurrence of open occlusion (Baik et al; Kalavritinos et al).…”
Section: Discussionmentioning
confidence: 99%
“…Removable appliances are widely used in the treatment of malocclusions. It has been shown that they improve dental and skeletal treatment outcomes [ 3 , 4 ]. Fränkel emphasized the importance of soft tissue impact, pointing out that abnormal craniofacial muscle tone plays a key role in the development of skeletal and alveolar defects.…”
Section: Introductionmentioning
confidence: 99%